Strategies for Improving the Quality of Islamic Education in Facing the Challenges of Modern Times - Hildayatin, Aghnii Luxiana; Helga, Clairien Devina; 'Arsyillah, Rahma Tahta; Syafi'i, Imam (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study aims to identify strategies to improve the quality of Islamic education in facing the challenges of modern times and technological developments. The method adopted is a literature study with a qualitative descriptive approach. The results show that the main challenges include the rapid development of information technology that can have a negative impact on student morals, as well as globalization that brings cultural values that are not always in accordance with Islamic principles. Strategies to improve the quality of Islamic education include modernizing education that focuses on Islamic principles and the times, utilizing technology to improve access to knowledge, and integrating traditional values with technology. Factors that influence the effectiveness of these strategies include the competence of educators, an adaptive curriculum, and sufficient infrastructure. This study concludes that efforts are needed to adapt the learning system to technological developments, integrate Islamic values  in a digital environment, and improve the competence of educators so that Islamic education remains relevant in the modern era.